2020
DOI: 10.1038/s41598-020-66866-1
|View full text |Cite|
|
Sign up to set email alerts
|

Diversity and function of terpene synthases in the production of carrot aroma and flavor compounds

Abstract: Carrot (Daucus carota L.) is an important root vegetable crop with high nutritional value, characteristic flavor, and benefits to human health. D. carota tissues produce an essential oil that is rich in volatile terpenes and plays a major role in carrot aroma and flavor. Although terpene composition represents a critical quality attribute of carrots, little is known about the biosynthesis of terpenes in this crop. Here, we functionally characterized 19 terpene synthase (TPS) genes in an orange carrot (genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
4
22
0
Order By: Relevance
“…The results observed in this study are in good agreement with findings reported in a very recent paper describing functional characterization of carrot TPSs 53 in the fully sequenced DH1 genotype 22 . This study also shows that the genomic region on chromosome 4 encodes TPSs catalysing the production of sabinene 53 . In complement to the findings of Muchlinski et al 53 we examined a sabinene-deficient carrot genotype.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The results observed in this study are in good agreement with findings reported in a very recent paper describing functional characterization of carrot TPSs 53 in the fully sequenced DH1 genotype 22 . This study also shows that the genomic region on chromosome 4 encodes TPSs catalysing the production of sabinene 53 . In complement to the findings of Muchlinski et al 53 we examined a sabinene-deficient carrot genotype.…”
Section: Discussionsupporting
confidence: 56%
“…This study also shows that the genomic region on chromosome 4 encodes TPSs catalysing the production of sabinene 53 . In complement to the findings of Muchlinski et al 53 we examined a sabinene-deficient carrot genotype. Taken together the complementary results of both studies are applicable in breeding programmes focused on modification of sabinene content in carrot.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, terpenes are important members of passion fruit VOCs, including linalool, (E) -4,8-dimethylona-1,3,7-triene 3-buten-2-one, terpinen-4ol, beta-ionone, and 3-carene. Terpenes are biosynthesized from the 5-carbon isoprenoid precursor isopentenyl-diphosphate (IDP) and its isomer dimethylallyl diphosphate (DMADP) 60 , and TPS enzymes then convert them into structurally diverse volatile monoterpenes and sesquiterpenes or semivolatile and nonvolatile diterpenes 61 . Terpenes are also abundant in many plants, such as the foliage of Eucalyptus 62 , tea tree 63 , coriander 64 and carrot 61 , providing the characteristic smell of these plants.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in previous studies ( 17 , 38 ), random forests' ability to consider multiple compounds simultaneously makes it suitable for analysis of patterns in VOC data. Random forests have been applied before to analyze VOC patterns for other settings [see e.g., ( 39 43 )], and the random forest-based variable selection algorithm Boruta has been deployed in other VOC studies too to select relevant compounds ( 44 48 ). In the present study, the Boruta algorithm was favored over other variable selection methods to reduce the number of VOCs to a set of potential MAP marker compounds because of its proven performance in the context of random forest classifiers ( 49 ).…”
Section: Discussionmentioning
confidence: 99%